Mechanisms of acetylcholine receptor loss in myasthenia gravis. - Drachman, D B (1980)
The fundamental abnormality affecting the neuromuscular junctions of myasthenic patients is a reduction of available AChRs, due to an autoimmune attack directed against the receptors. Antibodies to AChR are present in most patients, and there is evidence that they have a predominant pathogenic role in the disease, aided by complement. The mechanism of antibody action involves acceleration of the rate of degradation of AChRs, attributable to cross-linking of the receptors. In addition, antibodies may block AChRs, and may participate in producing destructive changes, perhaps in conjunction with complement. The possibility that cell-mediated mechanisms may play a role in the autoimmune responses of some myasthenic patients remains to be explored. Although the target of the autoimmune attack in myasthenic patients is probably always the acetylcholine receptors, it is not yet clear which of these immune mechanisms are most important. It is likely that the relative role of each mechanism varies from patient to patient. One of the goals of future research will be to identify the relative importance of each of these mechanisms in the individual patient, and to tailor specific immunotherapeutic measures to the abnormalities found.